1974
DOI: 10.1107/s0567740874002639
|View full text |Cite
|
Sign up to set email alerts
|

Some implications of combined X-ray and neutron diffraction studies

Abstract: A survey is made of about ten combined X-ray and neutron diffraction studies. The theory of X-N difference densities is reviewed for both centric and acentric structures. It is concluded that the phase problem has been incorrectly treated in past work on acentric crystals, leading to a systematic underestimate of the difference density. Expressions are given for the average standard deviation in the difference density due to random errors in both the X-ray and neutron measurements. A survey of experimental pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

1976
1976
1987
1987

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 11 publications
4
39
0
Order By: Relevance
“…An analysis of the positional parameters reveals shifts between 0.007 and 0.013 A for the X-ray positions of N(5), O(1), 0(2) and 0(3), the O atoms being shifted towards the lone-pair density while the nitro-group N is displaced into the C-N bond. The size of these shifts is as observed in other studies (Coppens, 1974) and indicates the dominant effect of low-order reflections even in a refinement including a large number of high-order data. It is of interest that while the shifts are reduced in the high-order refinement (sin0/~.>0.75 A -x, Table 2), systematic discrepancies persist for the four affected atoms, suggesting a persistence of valenceelectron scattering beyond 0.75 A -1.…”
Section: Molecular Structure and Asphericity Shiftssupporting
confidence: 65%
See 1 more Smart Citation
“…An analysis of the positional parameters reveals shifts between 0.007 and 0.013 A for the X-ray positions of N(5), O(1), 0(2) and 0(3), the O atoms being shifted towards the lone-pair density while the nitro-group N is displaced into the C-N bond. The size of these shifts is as observed in other studies (Coppens, 1974) and indicates the dominant effect of low-order reflections even in a refinement including a large number of high-order data. It is of interest that while the shifts are reduced in the high-order refinement (sin0/~.>0.75 A -x, Table 2), systematic discrepancies persist for the four affected atoms, suggesting a persistence of valenceelectron scattering beyond 0.75 A -1.…”
Section: Molecular Structure and Asphericity Shiftssupporting
confidence: 65%
“…Several earlier charge density studies of molecular crystals have clearly indicated the desirability of performing the necessary diffraction experiments at reduced temperatures (Verschoor & Keulen, 1971;Coppens & Vos, 1971;Coppens, 1974). Though the effect of thermal averaging on the density is becoming better understood in a quantitative sense (Coulson & Thomas, 1971;Ruysink & Vos, 1974;Coppens, 1975), reduction of the thermal smearing of the rest density and the corresponding increase in thermal resolution remain of considerable importance.…”
Section: Introductionmentioning
confidence: 99%
“…Since the space group Pna2~ is not centrosymmetric, special attention has to be paid to the phases of the contributions to the difference density. The phases of the amplitudes contributing to the X-N maps were calculated in the way suggested by Coppens (1974). The same procedure was applied by Thomas, Tellgren & Alml6f (1975).…”
Section: Comparison Of X-n Charge Distributionmentioning
confidence: 99%
“…For centrosymmetric structures the average standard deviations in the maps can be approximated by where f~ is the X-ray form factor multiplied by the amplitude of the radiation scattered by one electron and b~ is the scattering length for thermal neutrons (Coppens, 1974). For first row elements (f~) ~ (hi) but for compounds containing heavier elements these two factors will increase the average standard deviation.…”
Section: Table 4 Selected Interatomic Distances (A) and Angles (O) Wmentioning
confidence: 99%
“…The data for IDAB (X-ray) are taken from Oskarsson (1973). (4) tain information about deviations from spherical symmetry of the electron distribution around the atoms (Coppens, 1974). The quantities Fo.x-F¢,N are used as coefficients in Fourier summations.…”
Section: Table 4 Selected Interatomic Distances (A) and Angles (O) Wmentioning
confidence: 99%